Challenges in collaborative modelling: a literature review and research agenda. (10th March 2009) - Renger, Michiel; Kolfschoten, Gwendolyn L.; De Vreede, Gert-Jan
Modelling is a key activity in conceptual design and system design. Through collaborative modelling, end-users, stakeholders, experts and entrepreneurs are able to create shared understanding about a system representation. This paper reports on a literature review to provide an overview of the commonalities and differences in collaborative modelling research. We develop a framework of analysis and conduct a quantitative meta-analysis to understand the challenges in collaborative modelling. Next, we performed a qualitative analysis to further elicit these challenges and discuss requirements for tools to support collaborative modelling, using Group Support Systems (GSSs) or Interactive Whiteboards (IWBs). We found critical challenges in supporting the understanding and adoption of modelling rules, and in integration of sub-models and different perspectives of systems to achieve shared understanding visualised in a system representation.